Effective Approaches To Enhancing Connected Speech In Preoperative Children With Open Organic Rhinolalia - Adloyan, Lilit; Marukyan, Vera
Children with open organic rhinolalia, a condition often resulting from structural anomalies such as cleft palate, face unique challenges in speech development, particularly in the preoperative period. This article examines the methods, techniques, and strategies used to improve connected speech in these children before undergoing surgical intervention. Focusing on evidence-based practices, the article explores various speech therapy approaches, including breathing exercises, articulation drills, and resonance training, all tailored to address the specific needs of children with hypernasal speech. The goal of preoperative speech therapy is not only to prepare children for surgery but also to enhance their overall communication skills by developing clearer and more fluent speech. By reviewing current research and case studies, this article provides insights into effective treatment methods that can be applied in clinical settings to support children with open organic rhinolalia.
Keywords: Speech therapy